1990
DOI: 10.1116/1.576817
|View full text |Cite
|
Sign up to set email alerts
|

Model studies of dielectric thin film growth: Chemical vapor deposition of SiO2

Abstract: The reactive adsorption and decomposition of tetraethoxysilane is compared on Si(100) and SiO2 surfaces. The adsorption and decomposition behavior is compared to that observed for ethanol adsorption on both these surfaces. Tetraethoxysilane and ethanol both decompose to produce ethylene and hydrogen on Si(100). Ethylene desorption is also observed from decomposition of these molecules on SiO2. Ethanol adsorption on SiO2 is shown to model the chemistry of tetraethoxysilane on this surface. However, ethanol is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 0 publications
4
13
0
1
Order By: Relevance
“…[20,23] SiO 2 deposition from TEOS was found to be a self-limiting reaction in the absence of water or basic atmosphere. [20,28] Indeed, we also observed that the effect of the pretreatment did not vary with the amount of TEOS sprayed, even if large amounts of the TEOS/ ethanol mixture were used. This implies a film of SiO 2 is not grown under our conditions, but rather just a modification of the surface occurs.…”
Section: Teos Pretreatment Characterizationmentioning
confidence: 49%
“…[20,23] SiO 2 deposition from TEOS was found to be a self-limiting reaction in the absence of water or basic atmosphere. [20,28] Indeed, we also observed that the effect of the pretreatment did not vary with the amount of TEOS sprayed, even if large amounts of the TEOS/ ethanol mixture were used. This implies a film of SiO 2 is not grown under our conditions, but rather just a modification of the surface occurs.…”
Section: Teos Pretreatment Characterizationmentioning
confidence: 49%
“…When comparing TEM results from cases 1, 2, and 3 as detailed in Table 1, amorphous silica is present in all three, indicating that the ethanol and silicon nanoparticle solution contains a reactant (although no TEOS was added to the reaction), either free in solution or bound to the surface of the nanoparticle that is able to form amorphous silica in a Stöber reaction. Indeed, Crowell contends that the chemistry of TEOS can be modeled by ethanol adsorption on SiO 2 surfaces [24]. From case 2, TEM illustrates the formation of ∼30 nm silica particles which are slightly agglomerated with small necks.…”
Section: Ethanol Colloidmentioning
confidence: 99%
“…Because of the simplicity of the process and the superior film quality obtained, TEOS decomposition is the most frequently employed technique by the semiconductor industry for SiOz deposition (9)(10)(11)(12)(13)(14)(15). Moreover, this compound (TEOS) has less toxicity and is less hazardous to work with than conventional source gases, such as silane and chlorosilane (9).…”
Section: Low Pressure Chemical Vapor Deposition Of Silicon Dioxidementioning
confidence: 99%